Pengaturan Indonesianisasi Saham Melalui Divestasi Sebagai Refleksi Sumber Daya Alam Mineral Dan Batubara “Dikuasai Oleh Negara” - Hagrina Azkia Tamam (Universitas Islam Indonesia, 2019)
This study discusses first, amendments in the regulation of Indonesianization of Shares in Law Number 4 of 2009 and their impact on the country and the foreign investment. Second, whether the Indonesianization of shares through investment in Indonesian shares reflect the notion of “controlled by the state” is in accordance to what has been mandated in Article 33 point (3) of the Constitution of 1945. The research method used in this study is normative-juridical. The results of the study conclude that, first, amendments in the regulation on divestment of shares cause the lack of legal certainty for the State, the foreign investors, and the prospective foreign investors in the mining sector. Second, the divestment regulation of shares does reflect the notion of “controlled by the state” as mandated in Article 33 paragraph (3) of the Constitution of 1945